Shipboard ADCP current measurements (38 kHz) during RV METEOR cruise M189/2 - Ziegler, Steffen; Kopte, Robert; Kinne, Stefan (PANGAEA, 2023)
Current velocities of the upper water column along the cruise track of R/V Meteor III cruise MET189_2 were collected by a vessel-mounted 38 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 5.0 m below the water line. The instrument was operated in narrowband mode (WM10) with a bin size of 16.00 m, a blanking distance of 8.00 m, and a total of 80 bins, covering the depth range between 29.0 m and 1293.0 m. Heading, pitch and roll data from the ship's motion reference unit and the navigation data from the Global Positioning systems were used by the data acquisition software VmDAS internally to convert ADCP velocities into earth coordinates. Measured velocities and bin-depth mapping were corrected due to occasional incorrect temperature measurements at the transducer that affected the sound velocity calculation. Corrected sound velocity values were derived using temperature measured by the ship's thermosalinograph. The ship's velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship's heading data. Further errors stem from a misalignment of the transducer with the ship's centerline. Data post-processing included water track calibration of the misalignment angle (-44.9032° +/- 0.5594°) and scale factor (1.0036 +/- 0.0116) of the Ocean Surveyor signal. The velocity data were averaged in time using an average interval of 60 s. Velocity quality flagging is based on following threshold criteria: abs(UC) or abs(VC) > 1.5 m/s, rms(UC_z) or rms(VC_z) > 0.3.